2014
DOI: 10.1080/19322909.2014.901211
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ultimate Use Data and Its Implication for Digital Library Management: A Case Study

Abstract: Information professionals and librarians have been studying, discussing, and developing digital libraries for more than two decades, but understanding ultimate use of images from digital libraries remains a mystery for many of them. Most articles written on digital library use focus on users' search retrieval needs and behavior. Few mention how digital library patrons use the images they request. Like many digital libraries, archives, and special collections, the University of Houston Digital Library makes hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Assessing the impact of digital libraries and evaluating the use and reuse of digital objects for educational and personal use are growing areas of research interest. The case studies evaluating the reuse of digital objects involve analysis of user requests, tracking the use of images on the Web using reverse image lookup (Reilly and Thompson, 2014, 2017), or examining the reuse of digital library objects in Wikipedia (Kelly, 2018). The “Measuring Reuse of Digital Objects” project, undertaken by members of the Digital Library Federation’s Assessment Interest Group, focused on exploring the ways digital library materials are employed and reused (Kelly et al, 2018; O’Gara et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assessing the impact of digital libraries and evaluating the use and reuse of digital objects for educational and personal use are growing areas of research interest. The case studies evaluating the reuse of digital objects involve analysis of user requests, tracking the use of images on the Web using reverse image lookup (Reilly and Thompson, 2014, 2017), or examining the reuse of digital library objects in Wikipedia (Kelly, 2018). The “Measuring Reuse of Digital Objects” project, undertaken by members of the Digital Library Federation’s Assessment Interest Group, focused on exploring the ways digital library materials are employed and reused (Kelly et al, 2018; O’Gara et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may be tangible (incorporated into lectures, presentations, articles and artwork) or intangible (utilized for thematic illustration, intellectual reflection or inspiration” (p. 9). Her definition of ultimate use was adopted by Reilly and Thompson (2014), who examined intended image use by analyzing user requests received by the University of Houston Digital Library. Findings of this study indicate that images are primarily requested for personal use (35.6 per cent).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most widely documented methods for evaluating digital image reuse involves RIL services such as Google images or TinEye, in which an image is either uploaded or an originating URL is input to the search platform and then duplicates and similar images are found online. RIL studies have been performed on images from NASA, academic digital libraries, the Library of Congress, and the British National Gallery (Kelly, 2015;Kirton & Terras, 2013;Kousha et al, 2010;Reilly & Thompson, 2014;. In all of these studies, after duplicate images were found online, the context and purpose in which the images were reused was analyzed in order to determine who uses digital cultural heritage images and for what objective.…”
Section: Media Reuse Studiesmentioning
confidence: 99%